On Self-Induced Mental Incapacity from Article 24 of the Serbian Criminal Code - Turanjanin, Veljko; Ćorović, Emir (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
The authors in this work deal with the provision from Article 24 of the Serbian Criminal Code on self-induced mental incapacity. The legislator, through this provision, tries to solve problems, in theory known as actiones liberae in causa. The authors critically analyze this provision and indicate some unacceptable interpretations. In addition, they emphasize that some problems related to mental incapacity in some cases may be solved through other legal institutions from the criminal law.